The spectrum of cutaneous manifestations in COVID-19 patients at Dr. Cipto Mangunkusumo Hospital - Widaty, Sandra; Menaldi, Sri Linuwih Susetyo Wardhani; Miranda, Eliza; Marissa, Melani; Nilasari, Hanny; Melinda, Thong Felicia; Cornain, Emilina Faradila (UI Scholars Hub, 2024)
Background: Cutaneous manifestations are identified in 0.2%–20% of COVID-19 cases, both in adult and pediatric patients. They can occur before, simultaneously with, or after the systemic symptoms of COVID-19. This study aims to analyze the association between cutaneous manifestations, severity, and outcomes of patients with COVID-19. Methods: This observational study was conducted from April 2020 to April 2021 in Dr. Cipto Mangunkusumo Hospital, a referral center for COVID-19 in Jakarta, Indonesia. Medical records were used to collect demographic, clinical, and laboratory data. Results: A total of 0.61% (31/5070) of COVID-19 cases showed cutaneous manifestations, consisting of maculopapular (80.6%), vesicular (16.1%), livedoid (6.4%), pseudo-chilblain (3.2%), and urticarial (3.2%) lesions, with three patients showing more than one cutaneous manifestation. In the present study, only 2,001 out of 5,070 patients were appropriately confirmed to suffer from COVID-19 infection. Multisystem inflammatory syndrome in children (MIS-C) was identified in one out of eleven patients under 21 years old. Laboratory examinations showed an increased neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP), procalcitonin, D-dimer, and creatinine alongside a decreased albumin level. Conclusion: We reported various cutaneous manifestations and diagnostic test results associated with COVID-19. More than one cutaneous manifestations are present in several COVID-19 patients in our study. Several contradictory findings relative to previous publications indicate the necessity of collecting more data regarding the cutaneous manifestation of COVID-19.